Organization of rehabilitation programs for cancer patients based on an interdisciplinary approach - M. F. Ballyuzek; A. K. Ionova; M. V. Mashkova; B. P. Stepanov; O. L. Chagunava (Исследования и практика в медицине, 2018)
Purpose. To improve the technology of cancer patients' rehabilitation in the multidisciplinary hospital using an interdisciplinary approach at the stages of combined treatment of malignant tumors.Patients and methods. The analysis of 845 cases of admission of cancer patients in a multidisciplinary clinic for oncological rehabilitation, including treatment of complications and co morbid diseases, diagnosis and palliative care, on the specialized treatment stages was made. Based on the diagnosis, clinical status, determination of the clinical potential of these patients the need in medical rehabilitation of cancer patients based on the principles of an interdisciplinary approach was established.Results. A low commitment of oncologists to refer patients to multidisciplinary hospitals for supporting general medical treatment programs, which involve the work of multidisciplinary rehabilitation teams, especially at the initial stages of cancer, was revealed. In 94.1% of cases, based on oncologists' recommendation patients were presented to the multidisciplinary hospital only in the advanced stage of malignant disease. However, 64.8% of patients who came only for the purpose of "hospice" or palliative care treatment were able to continue their anticancer treatment. In 4.9% of cases among patients, who were referred for palliative care, the severity of their condition was mistakenly regarded as a relapse of cancer, whereas it was caused by comorbid pathology.The low interest of cancer patients in rehabilitation programs in the absence of recommendations from oncologists was revealed. It was shown that supportive therapy based on the principles of interdisciplinary approach is not only needed for patients with far-ongoing manifestations of cancer process, but also for patients with stage I-II of cancer, since even at this stage various complications of cancer disease, the consequences of its treatment and also manifestations of a combined pathology are often encountered.Conclusion. A classification of medical problems of cancer patients was proposed. Based on the newly developed methodology, the algorithm of personified rehabilitation support programs of oncological patients' and guidelines for managing patients at the stages of specialized and rehabilitative treatment using principles of an interdisciplinary approach, were created.